An explorative study to assess the factors influencing well-being of patients with End Stage Renal Disease (ESRD) undergoing hemodialysis at dialysis units of selected hospitals of Bagalkot - Torvi, Miss. Janhavi P; Joseph, Treesa; Natekar, Deelip S; P, Ashpak; ., Arun; M, Rekha; O, Sachin; ., Jicksy; B, Megha (International Journal of Membrane Science and Technology, 2023)
Background: Kidneys are paired organ, occupying the lower position in the body and performing the upper most roles in homeostasis. Nowadays, chronic kidney disease (CKD) has been increasing due to various factors. Chronic Renal Failure is defined by the level of kidney function and the evidence of kidney damage. End Stage Renal Disease (ESRD) is a known increasing public health concern globally. The irreversible advanced CKD leads to End Stage Renal Disease (ESRD) where there is permanent loss of kidney function causing extreme mortality rates among this population1 Objective: Find the factors influencing wellbeing of patients with End Stage Renal Disease (ESRD) undergoing hemodialysis. Methods: This cross-sectional study included a sample of 100 patients with End Stage Renal Disease (ESRD) undergoing hemodialysis at Hanagal Shri Kumareshwar Hospital and Research Centre, Bagalkot and District Government Hospital, Bagalkot. Data were collected using self report method and Hospital’s records. Tools used for data collection were; socio-demographic questionnaire, Ryff’s Psychological Wellbeing scale and Centre for Epidemiologic Studies Depression Scale (CES-D Scale), Generalized Anxiety Disorder Scale – 7 (GAD-7). Multiple linear regression analysis was performed to find the significant predictors of Psychological Wellbeing. Results: A significant regression equation was found (F16, 99=4.5, R2=0.46, P=0.000). Social Support has positively predicted the Psychological Wellbeing of patients with End Stage Renal Disease (ESRD) undergoing hemodialysis. Depression and Anxiety was the strongest negative predictors of Psychological Wellbeing of patients with End Stage Renal Disease (ESRD) undergoing hemodialysis. Conclusion: Interventions aimed at management of depression, anxiety and strengthening of social support among patients with End Stage Renal Disease (ESRD) undergoing hemodialysis would result in enhancement their Psychological Wellbeing.